A study on the applicability of the efficiency factor of supplementary cementitious materials to durability properties. (1st September 2016) - Lollini, Federica; Redaelli, Elena; Bertolini, Luca
Highlights: Efficiency factor k is often used as a practical approach for determination of the role of SCMs on concrete strength. The applicability of k -values to durability-related properties is questionable. Strength-derived k -values showed to be appropriate as a proxy-criterion only for carbonation resistance. Specific k -values are needed for chloride-resistance performance. These k -values were around 1.5 for fly ash and slag and lower than 1 for ground limestone and pozzolan. Abstract: Supplementary cementitious materials (SCMs), such as fly ash, pozzolan or blastfurnace slag, are widely used to produce blended portland cements, since they lead to a significant reduction in CO2 emission in the production phase compared to portland cement. A practical and generally accepted approach to evaluate the contribution of SCMs to the strength of the hardened concrete is through the concept of the SCMs efficiency factor (i.e. k -value concept), which expresses the fraction of portland cement that can be replaced by a SCM at unchanged strength. In the literature some studies have also been focused on the use of the k -value approach also for the resistance against carbonation and chloride penetration of blended portland systems. However, limitations of applicability of SCMs efficiency factor to durability properties are not clear. In this paper the k -value of different SCMs, such as ground limestone, fly ash, natural pozzolan and ground granulated blastfurnace slag, was investigated to detect firstly if it can be applied to carbonation- and chloride-related properties and, secondly, if strength can be considered as a proxy-criterion for durability properties. Results showed k -values lower than 1 for all the SCMs with respect to compressive strength and that these values were valid also for resistance to penetration of carbonation. As far as the resistance to chloride penetration is concerned, k -values derived from strength tests were not applicable and specific k -values should be evaluated; values higher than 1 were calculated for fly ash and ground granulated blastfurnace slag, whilst values lower than 1 were obtained for ground limestone and natural pozzolan.